2021
DOI: 10.30603/al.v7i2.2217
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Emergence of Digital Platforms for Listening Learning Proficiency

Abstract: This study investigates the use of any platforms in English language teaching and learning, especially in listening skills. This research design is qualitative. From the result, it shows that some technologies available both online or offline include applications or platforms that provide many choices for listening to English, they are. 1) Music platform. These platforms can be found in PlayStore, such as Joox and Spotify recommends songs for listening skills. 2) Youtube channel. Many YouTube channels for lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…The language skills as well as cognitive that offered by technology is much better than what those teachers' have given. This is in line with students' response which is found by Khan et al (2021) [7] that students' response towards the use of technology was positive and was fun to be used in learning activity. The result of their result show that during the learning activity got the higher result.…”
Section: Introductionsupporting
confidence: 84%
“…The language skills as well as cognitive that offered by technology is much better than what those teachers' have given. This is in line with students' response which is found by Khan et al (2021) [7] that students' response towards the use of technology was positive and was fun to be used in learning activity. The result of their result show that during the learning activity got the higher result.…”
Section: Introductionsupporting
confidence: 84%
“…The hyphotheis test result showed that using digital audio for learning media can improve students' abilities compared to only using direct speech. Similar studies on the use of digital audio in learning materials for EFL learners can be found in (Fitria, 2021) and (Ayatfard, 2022), which shows that the application of EFL helps students' listening skills.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, developing listening skills can be made more enjoyable to prevent boredom. The average of their pre-test, post-test I, and post-test II scores was noticeably higher (Fitria, 2021). Making use of technology, such as digital audio, can help students learn how to improve their listening skills.…”
Section: Introductionmentioning
confidence: 90%
“…Besides audio, VOA Learning English also offers a video version. As the name implies, Voice of America (VOA), Fitria (2021b) states that VOA is one of the channels for learning Listening English with the American Style.…”
Section: Discussionmentioning
confidence: 99%